Ein eisenzeitlicher Hofplatz mit erhaltener nutzungszeitlicher Laufoberfläche in einem Dünental auf der Insel Amrum (Nebel LA 431): Overgangen mellem sten- og bronzealderen ved Revsinggård II - Unglaub, Christoph; Klooss, Stefanie; Blankenfeldt, Ruth (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The western part of the North Frisian island of Amrum is characterized by a wide area of sand dunes. Beneath the dunes the old geest landscape with prehistoric settlement sites and burial grounds is preserved. At the wind exposed site Nebel LA 431 near the duck decoy Meeram uncovered structures were documented and small exploratory excavations were carried out between 2020 and 2022. Using modern methods, a farmstead of the late pre-Roman Iron Age / early Roman Imperial Period is being investigated here. Several settlement sites had already been documented by Hans Hingst in the 1960s and 1970s in the nearby surroundings. The former occupation layer of the settlement is characterized by extensive stone pavements. These are partly covered by a massive cultural layer containing burnt clay, marine clay, charcoal, and numerous pottery sherds. In addition to a courtyard pavement preserved over an area of about 25 m², in which a large pit and a fireplace are embedded, it was possible to document at least two socalled manure gutters, carefully set out of stones and representing the longitudinal central passage in the livestock barn section of the longhouse. Several oval hearths, paved and partly covered with a clay mantle, indicate the living part of the house. Intensive traces of fire in the living quarters suggest that this part of the house had to be renewed at least once and that several settlement phases presumably overlap here. Furthermore, an old soil with Neolithic flint artifacts beneath the Iron Age settlement layer indicates older settlement phases.